Is virtual reality (VR) a future trend in nursing education? - LIAO, Qian Ye; HSU, Mei Hua Kerry (Edelweiss Applied Science and Technology, 2024)
Background: Virtual reality (VR) has been developed and applied diversely from aviation into education. VR can help students for immersive experiences from different scenarios. In this regard, nursing educators play an important role in effective VR application. The feature aspects of VR in nursing education included safety, convenience, motivation, and interactivity. The challenges of VR in nursing education were related to participants’ recruitment and selection, as well as the budget and settings. The future VR in nursing education must be VR equipment well supported including maintenance, user friendly to better learning experiences among nursing students, reasonable budget and funding for the technology learning environment, and preparation of nursing educators to become more innovative in the application of VR in nursing. What this paper contributes: This paper aims to discuss the current VR application and the future aspects in nursing education. Nursing education should have the new aspects and views supported by the technology to improve nursing students’ comprehensive competencies for the better nursing cares in the future.